2008
DOI: 10.1111/j.1440-1843.2008.01239.x
|View full text |Cite
|
Sign up to set email alerts
|

Stable prevalence of asthma symptoms in school‐aged children in the Torres Strait region

Abstract: Asthma prevalence in school-aged children living in the Torres Strait region remains high but, as in mainstream Australian children, the prevalence is stable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…The prevalence of asthma symptoms was also studied in the Torres Strait region of Northern Australia, and the findings were compared with two previous studies. The investigators found a stable prevalence of various indices that included self‐reported wheeze (12.5%), exercise induced wheezing (5.9%) and having asthma (12.2%) 5 . The findings were broadly similar to the results of surveys done in mainland Australia, and the increase in asthma prevalence noted in recent years appears to have reached a plateau.…”
Section: Asthmasupporting
confidence: 64%
“…The prevalence of asthma symptoms was also studied in the Torres Strait region of Northern Australia, and the findings were compared with two previous studies. The investigators found a stable prevalence of various indices that included self‐reported wheeze (12.5%), exercise induced wheezing (5.9%) and having asthma (12.2%) 5 . The findings were broadly similar to the results of surveys done in mainland Australia, and the increase in asthma prevalence noted in recent years appears to have reached a plateau.…”
Section: Asthmasupporting
confidence: 64%
“…The cross-sectional study took place on 4 island communities: Thursday Island, Horn Island, Sue Island, and Mabuiag Island. Further details of the study have been previously described [22]. Briefly, the study was conducted in this region from April to September, 2003, in conjunction with a general health-screen program initiated by the local health district.…”
Section: Methodsmentioning
confidence: 99%
“…Measurements included height, weight, and waist circumference (standardisation of these measurements have been described elsewhere) [22]. The majority of the data was collected by a nutritionist of Aboriginal descent (AM) and on the occasions by an Indigenous health worker.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 158 youth described in this study were aged between 5 and 17 years and attended one of two primary schools on either Mabuiag Island (47 youth, 96% response rate) or Sue Island (43 youth, 100% response rate), or the high school on Thursday Island as boarders (68 youth, 97% response rate) since their families resided in the outer Torres Strait Islands. Full details of study design have been described elsewhere (12). Ethical approval was obtained from the Queensland Institute of Medical Research Human Ethics Committee.…”
Section: Methodsmentioning
confidence: 99%